2015
DOI: 10.1007/s11205-015-1061-z
|View full text |Cite
|
Sign up to set email alerts
|

Can Social Capital Affect Subjective Poverty in Europe? An Empirical Analysis Based on a Generalized Ordered Logit Model

Abstract: In a previous exploratory analysis of the 2009 EU-SILC survey and the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 47 publications
2
24
0
Order By: Relevance
“…The single parent in our sample, therefore, might benefit of the help of a network of relatives/informal network for childcare. The importance of such a form of social capital on SP perception is confirmed by the existing literature (see, for instance Guagnano et al 2016).…”
Section: Analysis Of the Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…The single parent in our sample, therefore, might benefit of the help of a network of relatives/informal network for childcare. The importance of such a form of social capital on SP perception is confirmed by the existing literature (see, for instance Guagnano et al 2016).…”
Section: Analysis Of the Resultssupporting
confidence: 68%
“…Other levels in the answer are with difficulty, with some difficulty, fairly easily, easily, very easily. In general, this evaluation of the economic status will be influenced by both the current and the permanent income (Whelan and Maitre 2010), but also the social capital (Guagnano et al 2016) and social environment in which the household lives (Buttler 2013). This measure does not depend on a national or local threshold, although subjective evaluation will be influenced by social construction of necessary expenses.…”
Section: Alternative Poverty Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…has their willingness to engage with government or to help the environment. This decline may not be without consequence: Two European studies have found that increased social capital can improve poor households' ability to make ends meet (Guagnano, Santarelli, & Santini, 2016), and that increased social capital is associated with increased levels of happiness (Rodríguez-Pose & von Berlepsch, 2014).…”
Section: Beyond Misinformation 16mentioning
confidence: 99%
“…Thus Temple and Johnson (1998) Next, we turn to the impact of social capital on well-being. To date, studies on this topic have focused on cross country evidence (Bartolini, Mikucka, & Sarracino, 2017;Bjørnskov, 2003;Pugno, 2009) as well as individual countries either developed (Guagnano, Santarelli, & Santini, 2016;Portela, Neira, & del Mar Salinas-Jiménez, 2013;Sarracino, 2014) or developing. The latter includes analysis on Pakistan (Ahmed, Sadaqat, & Bilgrami-Jaffery, 2014), Nigeria (Adepoju & Oni, 2012), and Vietnam (Turner & An Nguyen, 2005) while those specifically on rural areas have focused on Burkina Faso (Christian Grootaert, 1999), Tanzania (Narayan & Pritchett, 1997), and Indonesia (Christian Grootaert, 1999).…”
Section: Literature Review On Social Capital and Well-beingmentioning
confidence: 99%